The effect of macroeconomic variables on exchange rate: Evidence from Ghana - Samuel Antwi; Mohammed Issah; Aboagyewaa Patience; Solomon Antwi (Cogent Economics & Finance, 2020)
The study examined the effect of macroeconomic variables on exchange rate in Ghana using a multivariate modeling technique of the Vector Autoregression (VAR) and focusing on impact of broad money supply (M2), lending rate, inflation and real GDP on exchange rate, for 76 quarterly observations period of 2000-2019, in Ghana and to examine their effectiveness in managing exchange rate in Ghana. The study used only secondary sources of data from Bank of Ghana, World Development Indicators and Ghana Statistical Service. It was found that, real GDP granger causes exchange rate in Ghana. However, inflation, money supply and lending rate do not granger cause exchange rate in Ghana but they affect exchange rate indirectly. It was recommended that a sound exchange rate policy should take into account some considerations. The bank of Ghana should try to reduce the lending rate and money supply in order to lower inflation to create rooms for more investors to produce more to increase the GDP produced in the country, in order to depreciate the foreign currency.
Keywords: 330; broad money supply (M2); exchange rate; inflation; lending rate; macroeconomic variables; real GDP; vector autoregression (VAR)